Abdominal and pelvic tumours in children. Issue 5 (May 2022) - Sidebotham, Emma
Abstract: While all childhood cancers are rare, the abdomen and pelvis are common sites of origin. After haematological malignancies and intracranial tumours, neuroblastoma is the most common childhood cancer, most often arising in the adrenal gland. The next most common extracranial tumours are Wilms tumour, arising in the kidney (nephroblastoma) and rhabdomyosarcoma that may arise in a variety of sites, typically in the pelvis. Hepatoblastoma, non-Hodgkin lymphoma and germ cell tumours are other abdominal and pelvic tumours seen in childhood. Many childhood tumours appear to arise from residual embryonic cells which make them sensitive to chemotherapy and radiotherapy. Surgery plays a crucial role both in establishing the diagnosis and, in the majority of cases, by resection of the tumour.